DEVELOPMENT IN STRING THEORY (Journal of Sciences, Islamic Republic of Iran)
The string theory is a fast moving subject, both physics wise and in the respect of mathematics. In order to keep up with the discipline it is important to move with new ideas which are being stressed. Here I wish to give extracts from new papers of ideas which I have recently found interesting. There are six papers which are involved: I ."Strings formulated directly in 4 dimensions " A. N. Schellekens II. "Remarks on 40 strings" C.Bachas III. "Informal introduction to extended algebras and conformal field theories with c 1 " F.Ravanini IV. "Skein relations and braiding in topological gauge theory" and "Modular geometry and the classification of rational conformal field theories " S. Mukhi V. "Chern-Simons theories" E. Witten VI. "Duality and the rdl of nonperturbative effects on the world-sheet" J.Lauer, J.Mas and H.P. Nilles